Stancu Polynomials Based on the $q$-Integers (Analysis in Theory and Applications, 2012)
A new generalization of Stancu polynomials based on the $q$-integers and a nonnegative integer $s$ is firstly introduced in this paper. Moreover, the shape-preserving and convergence properties of these polynomials are also investigated.